Correlation between blood type and SARS-CoV-2 infection susceptibility: A literature review - Boavantura, Bianca Larissa Silva; Mendonça, Eliane Pereira; Izidoro, Luiz Fernando Moreira (Seven Editora, 2023)
The pandemic caused by SARS-CoV-2 is one outbreak that affects human health worldwide. Since the first confirmed case, several people have been infected across the globe and many have unfortunately lost their lives due to complications caused by Covid-19. Several studies have been published on the subject since the disease emerged, and among these, studies correlating blood type and levels of infection by SARS-Cov-2. The purpose of this work is to collect works published on the subject, during the period of 2020 and 2021, and to investigate whether it is possible to prove the existence or non-existence of this correlation. Articles were searched in 3 databases, and reaching a final number of 44 analyzed articles. Concluding a greater susceptibility to infection in individuals of type A and group O being considered protective against infection. DOI:https://doi.org/10.56238/emerrelcovid19-055